Mediation effect of emotions on relational dynamics between entrepreneurs’ thinking processes and their entrepreneurial decision-making - Sanda, M.; Sallama, M. (Journal of the International Council for Small Business, 2023)
This study provides understanding of how creative entrepreneurs’ thinking processes affect their entrepreneurial decision-making and the influencing role played by their emotions. Using a cross-sectional design, quantitative data were collected from 576 creative entrepreneurs and analyzed descriptively and inferentially. It was found that creative entrepreneurs’ thinking processes affect their entrepreneurial decision-making. Their emotions were also found to strongly negatively affect their entrepreneurial decision-making. It was concluded that in understanding how the thinking processes of creative entrepreneurs inform their entrepreneurial decision-making and their emotional orientations, which strongly determine the character of their entrepreneurial decision-making must be considered. The results of this study provide a good understanding of the dynamics of creative entrepreneurs’ thinking processes and their entrepreneurial decision-making and the mediating influence of their emotions, which could be used to effectively design creative entrepreneurship skills and practices toward improved entrepreneurial decision-making.
Research Article
Keywords: Entrepreneurs’ thinking processes; entrepreneurial decision-making; creative entrepreneur industry